Logistic Performance Measurement on a Port in Aceh - Prima Denny Sentia; Regita Ramadani; Sarika Zuhri (Institute of Research and Community Outreach - Petra Christian University, 2018)
Indonesia government has established sea toll program through Presidential Regulation No.17 in 2017 to support inter-island distribution. Port X in Aceh is one of the ports included in sea toll program. This paper discusses logistic performance m.easure, especially in sea transportation. A Logistic Performance Index (LPI) is proposed as a tool to identify challenges and opportunities in Port X performance. Key indicators which affect the value of logistics performance index will also be studied in this paper. There are several logistic performance measurements for port X based on literature study: quality, delivery cost, transportation cost, and information. Eight indicators affect Port X performance: quality of the commodity, the quantity of the commodity, on time delivery, ship call, sea transportation cost, storage cost, electronic availability, and electronic access. Port X average total index, based on Analytical Hierarchy Process, is 2,557. This value can be considered as quite reasonable. The study limits logistic performance for the arrival route of the container vessel leading to Port X. The final result shows that quality performance indicator (quality quantity of commodity index) has the highest index for all originating port. The second highest index is electronic information availability index. Through this finding, Port X must improve their service and information because it plays a vital role in their performance